Safety and efficacy of the COMBO bio-engineered stent in an all-comer PCI cohort: 1-Year final clinical outcomes from the MASCOT post-marketing registry. (15th May 2019) - Colombo, Antonio; Chandrasekhar, Jaya; Aquino, Melissa; Ong, Tiong Kiam; Sartori, Samantha; Baber, Usman; Lee, Michael; Iniguez, Andres; Hajek, Petr; Borisov, Borislav; Atzev, Borislav; Den Heijer, Peter; et al.
Abstract: Background: The COMBO stent (OrbusNeich Medical, Ft. Lauderdale, Florida) is a new-generation bio-engineered drug eluting stent, combining an abluminal coating of a bioabsorbable polymer matrix for sustained release of sirolimus and luminal anti-CD34 coating for endothelial progenitor cell capture and rapid endothelialization. Methods: The Multinational Abluminal Sirolimus Coated BiO-Engineered StenT (MASCOT) registry was a prospective post-marketing study conducted from June 2014–May 2017 across 60 centers globally. Patients were eligible if COMBO stent implantation was attempted, and they received dual antiplatelet therapy (DAPT) per local guidelines. Follow-up was conducted by trained research staff at 1, 6 and 12 months by phone or clinic visit to capture clinical events and DAPT cessation events. The primary endpoint was 1-year target lesion failure (TLF), composite of cardiac death, non-fatal myocardial infarction not clearly attributable to a non-target vessel, or ischemia-driven target lesion revascularization. Results: A total of 2614 patients were enrolled over the study period with 96.7% completion of 1-year follow-up. The mean age of enrolled patients was 62.9 ± 11.2 years and 23.0% were female. Diabetes mellitus was present at baseline in 33.5%. A total of 56.1% patients underwent PCI for acute coronary syndrome (ACS). The 1-year primary endpoint of TLF occurred in 3.4% patients ( n = 88). Definite stent thrombosis occurred in 0.5% patients ( n = 12). Conclusion: The MASCOT post marketing registry provides comprehensive safety and efficacy outcomes following contemporary PCI using the novel COMBO stent in an all-comer population. This platform is associated with low rates of 1-year TLF and ST. Clinicaltrials.gov identifier: NCT02183454 . Highlights: The COMBO stent is a new-generation drug eluting stent (DES) combining sirolimus elution and endothelial progenitor cell capture for rapid endothelialization. The Multinational Abluminal Sirolimus Coated BiO-Engineered StenT (MASCOT) registry enrolled 2614 patients with attempted COMBO stent implantation across 60 centers globally. COMBO DES was associated with low rates of 1-year TLF, ST and MACE with high rates of device and procedural success.